The Advantages of the Uswah Hasanah Method in the Perspective of Q.S. Al-Ahzab Verse 21: Conceptual Analysis and Implementation - Muhammad Thoriqul Islam; Fatma Amelia; Moh Ulul Azmi; Safiruddin Al Baqi; Sulton Muzakki; Ida Nur Oktaviani; Dwiana Novitasari; Ummu Habibah (Universitas Sebelas Maret, 2025)
Adverse social environments can affect students' attitudes, even though educators try to provide good examples. The influence of peers and the surrounding culture is often more substantial, making it easier for students to imitate negative behavior. To overcome this, educators must be accurate role models in everyday life, both inside and outside the classroom. Consistent role models will inspire students to imitate positive behavior. Educators also need to continue to improve their quality, referring to the principles of QS. Al-Ahzab verse 21, to strengthen role models and build students' social involvement. This study uses a qualitative text study method with literature studies, relying on various relevant library sources. Data were analyzed using content analysis to identify themes related to the advantages of the uswah hasanah method from the perspective of QS. Al-Ahzab verse 21. The study results show that this verse emphasizes the Prophet Muhammad SAW as the best role model with noble qualities such as patience, honesty, and sacrifice. The uswah hasanah method can be formulated into three main aspects: first, a Perfect Example, covering spiritual, social, and moral aspects; second, Good Worship Practices, teaching the implementation of worship with full attention; Third, Implementation in Education, using the Prophet's morals to shape students' characters. Thus, the uswah hasanah method is effective in Islamic education and in forming noble characters